ANALISIS DETERMINAN PENDAPATAN PEKERJA PEREMPUAN (RUMAH TANGGA MISKIN) DI KECAMATAN UTAN - Wahyu Haryadi; K Kamaruddin; Deni Septiadi (Pusat Riset dan Publikasi, 2020)
This study was conducted on poor household women workers in Utan sub-district. This study aimed to know the effect of work, education level and working hours toward the income of poor female household workers in Utan District, either partially or simultaneously. The type of this study was associative with quantitative data types. The data in this study were primary and secondary. The data collection technique used was interviews. The data analysis techniques used were multiple linear regression, statistical T and F test. The results of the simultaneous test (F-test) showed that work, level of education and working hours together have a significant effect toward the income of poor female household workers in Utan District. Based on the results of the partial test (t-test), the results of this study indicated that the work partially had a positive and significant effect toward the income of poor female household workers, the level of education partially has a negative and significant impact toward the income of poor female household workers, and working hours partially did not affected the income of women workers in poor households.